2015
DOI: 10.1183/13993003.01274-2015
|View full text |Cite
|
Sign up to set email alerts
|

The INPULSIS trials of idiopathic pulmonary fibrosis treatment: explaining further discrepancies on exacerbations

Abstract: In a recent paper on the INPULSIS trials, two duplicate 1-year randomised controlled trials evaluating nintedanib in the treatment of idiopathic pulmonary fibrosis (IPF) [1], we provided the methodological explanation for the apparent inconsistent results arising from the two different definitions of exacerbations used in those studies [2]. These trials reported vastly different findings in their pooled analysis [1]. Indeed, the risk of an investigator-reported acute exacerbation was lower by 36% with nintedan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…When only adjudicated acute exacerbations were analyzed, both INPULSIS studies had a reduced frequency of acute exacerbations on nintedanib. 69 Thus, nintedanib reduces both the rate of FVC decline and frequency of acute exacerbations in IPF. It was FDA approved for this indication in 2014.…”
Section: Clinical Evidence For the Use Of Antifibrotics In Ipfmentioning
confidence: 99%
“…When only adjudicated acute exacerbations were analyzed, both INPULSIS studies had a reduced frequency of acute exacerbations on nintedanib. 69 Thus, nintedanib reduces both the rate of FVC decline and frequency of acute exacerbations in IPF. It was FDA approved for this indication in 2014.…”
Section: Clinical Evidence For the Use Of Antifibrotics In Ipfmentioning
confidence: 99%
“…Other studies also identified a positive effect of a treatment with RTX with plasma exchange and intravenous immunoglobulin, polymyxin B-immobilized fiber column perfusion in patients diagnosed with IPF and intravenous thrombomodulin in CTD patients [159,164]. Recently, the effective use of Nintedanib in AE in IPF patients has been described in two patients [165,166], and, of note, in INPULSIS-2 trial there was a significant difference between the nintedanib and placebo groups in the time to the first acute exacerbation (hazard ratio, 0.38; 95% CI, 0.19 to 0.77; p = 0.005), even if the reliability of this result is still controversial [167,168].…”
Section: Pharmacological Treatmentmentioning
confidence: 99%